PERTUMBUHAN DAN HASIL KACANG BOGOR (Vigna subterranea (L.) Verdc.) VARIETAS LOKAL LEMBANG DI KALIMANTAN SELATAN - Ramadhani Kurnia Adhi; Soleh Wahyudi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This research is aimed to study growth and yield of Bambara groundnut Lembang variety which is cultivated in South Kalimantan. A descriptive exploratory research was conducted in field of National Agricultural Training Center Binuang Tapin Regency, South Kalimantan Province on July to November 2017. Observations were made on plant growth component i.e. germination time, number of main branch, flowering age, flower number per branch, harvesting age, pest and disease. Observations were made on yield component i.e. number of pods per plant, wet pods weight per plant,  wet pods weight per plot, 100 seed weight, proportion of wet pods weight, dry pods weight and dry seed weight. The results showed that Bambara groundnut Lembang variety flowering at the age of 43 to 65 days and harvesting at the age of about 115 to 120 days. Average number of pods are 40 pieces with an average weight are 90,76 grams of pods per plant. Bambara groundnut Lembang variety have potential yield of 11,524 tons per hectare of wet pod or 2,881 tons per hectare of dry beans. Thus, Bambara groundnut Lembang variety have the potential to be developed in South Kalimantan.